Management of introduced American bullfrogs (Lithobates catesbeiana Shaw 1802) in the South Okanagan, British Columbia - Lukey, Natasha (University of Waterloo, 2017)
Introduced invasive species threaten biodiversity on a global scale. An estimated fifteen new species introduction and establishments occur in aquatic systems per decade in Canada. A particular introduced aquatic species of concern in western Canada is the American bullfrog (Lithobates catesbeianus; formerly Rana catesbeiana, Shaw 1802; hereafter referred to as bullfrogs). Bullfrogs were introduced into one wetland in the South Okanagan, British Columbia in the 1950s for human consumption, and have since been detected in 7 locations across 5 wetland complexes. Bullfrog populations were detected by biologists in the South Okanagan in 2003, and shortly after intense bullfrog control efforts were initiated. On-going, resource-intensive detection and removal efforts targeting all life stages were put into place in 2004. Limited resources and lowered detections are prompting the need to determine the potential re-colonization patterns and effort required to successfully continue to suppress populations. Determining potential colonization patterns and optimal future control measures for bullfrogs in the South Okanagan is also of critical importance to the conservation of native amphibians, 50 % of which are federally threatened, endangered, or of special concern. Introduced bullfrogs outcompete, predate upon, transmit disease to, and interfere with reproductive activity of native amphibians. The goals of this thesis were to: 1. develop a distribution model for introduced bullfrogs in the South Okanagan, to: a. estimate the distribution probability of bullfrogs previous to major wetland landscape changes beginning in 2004; and b. project the historical distribution onto the changing wetland landscape post 2004 to prioritize monitoring during average annual wetland conditions, and consecutive flood and drought years anticipated with a changing climate; 2. Analyze nine years of existing introduced bullfrog detection and removal effort in the South Okanagan, to: a. describe the methods, total effort, and results of the bullfrog management; and b. highlight key management lessons learnt through bullfrog control in the South Okanagan. Goal 1 was addressed using species distribution modeling with Maxent®. The distribution model aimed to create a wetland-specific probability distribution for bullfrogs in the South Okanagan for 235 wetlands across a 233 km2 extent. Hydroperiod, water velocity, surrounding matrix at 100 m, 500 m, and 1000 m, distance to nearest known breeding location, and presence of introduced predatory fish were modeled using a minimum training presence threshold to determine wetlands at highest risk of bullfrog colonization and projected onto the future wetland landscape under the 3 scenarios. Maps were validated using 28 % partitioned test data and evaluated using Area Under the Curve and True Skill Statistics. Following Maxent modeling, mapped wetlands were ranked in ArcGIS according to presence of provincially endangered or threatened native amphibian species and number of neighboring wetlands within a 1000 m buffer. Permanent, stagnant, large ponds surrounded by high cover/moisture retaining agriculture (i.e. tree fruit orchard), within 300 m of a breeding location are at highest risk of bullfrog colonization. 60.5 %, 71.5 %, and 47 % of the South Okanagan wetlands are classified for priority monitoring and carry a relative rank value of 0.5 or higher in typical, flood, and drought conditions, respectively. The resulting wetland landscape map from the present study is a water body ranked priority monitoring list for all known permanent and ephemeral wetlands in the study area. The bullfrog distribution map provides wetland criteria, and the ranked monitoring priority list highlights key areas in which to focus future bullfrog monitoring efforts within the South Okanagan. Goal 2 was addressed using the wetland monitoring and bullfrog removal collective data set obtained from the BC Ministry of Environment, BC Ministry of Forests, Lands, and Natural Resource Operations, Environment and Climate Change Canada, and the University of Waterloo, Canada. Bullfrog detection and removal effort resulted in 11 102 introduced individual bullfrogs and egg masses detected and removed at 7 of the 125 surveyed sites in the South Okanagan between 2004 and 2012, with zero detections occurring in 2011 and 2012. Main detection and removal effort included auditory surveys, active searches, Gee trapping, and night-time canoe searches. Approximately 640 and 850 total search hours were expended for auditory and active searches respectively, and 24 670 total 24-hour trap day equivalents of Gee trapping. An additional 310 hours were spent on night-time canoe searches, 2 940 hours were spent on automated auditory recording, and 65 hours on seine netting and night-time active searches by foot. The catch per unit effort (CPUE) of the main methods varied widely among methods and sites, from 0 to 16 ± 55 individuals per trap day for Gee trapping, to 0 to 41 ± 46 individuals per search hour for active searches, and 0 to 28 individuals per hour for canoe searches. Although statistical comparison of methods is precluded due to the post-hoc nature of this analysis, results indicate that the combination of methods selected was successful in reducing abundance at the colonized ponds. However, the variation in CPUE supports the premise that effort needs to be maintained for detection and removal in subsequent years as there are likely additional individuals at low enough densities to avoid detection by standard methods. Here I recommend 10 years of zero detections, based on the Committee for the Status of Endangered Wildlife in Canada (COSEWIC)’s threatened species population trend assessment guidelines. Major lessons learned include: each water body requires an adaptive and robust approach; removal efforts must be persistent; future monitoring should focus on a slight increase in visual effort and slight reduction in auditory effort when populations are at low abundances; and repetitive training is required for observers to ensure accurate identification. The future of bullfrog control in the South Okanagan presents challenges under low population abundance and low detectability, and reduced funding while population suppression is at a critical point in preventing re-establishment. Multiple collaborative efforts combining different agency goals and target species is recommended to help alleviate the resource-limiting pressure for monitoring. Ultimately, the results of this thesis suggest permanent, stagnant, ponds surrounded by high cover/moisture retaining agriculture (i.e. tree fruit orchard), within 300 m of a breeding location are at highest risk of bullfrog colonization, and monitoring should focus on a slight increase in visual effort and slight reduction in auditory effort when populations are at low abundances.
Keywords: American Bulfrog; Lithobates catesbeiana; Introduced invasive species; Habitat suitability model; invasive species control; frogs; animal introduction; wetland ecology; wetland conservation; Okanagan Valley (Region); British Columbia